PENGARUH MODEL PEMBELAJARAN REACT (RELATING, EXPERIENCING, APPLYING, COOPERATING, TRANSFERRING) TERHADAP HASIL BELAJAR GEOGRAFI PESERTA DIDIK KELAS X.E DI SMA NEGERI 1 SALIMPAUNG - isnaini, indri; Mariya, Sri (JURNAL BUANA, 2024)
This study aims to determine the influence of the REACT Learning Model (Relating, Experiencing, Applying, Cooperating, Transferring) on the geography learning outcomes of grade X.E students at SMA Negeri 1 Salimpaung. The type of research used is a quantitative approach with a quasi-experimental method. Sampling using the Cluster random sampling technique, and two classes were selected, namely class X.E 2 (experiment) with 32 students, and class X.E3 (control) with 32 students. The research instrument is in the form of a 20-point test question. The average learning outcomes of students in the experimental class were 86.87, the control class was 82.96. In the experimental class, an increase in N-Gain knowledge of 0.76 was obtained in the high category. While in the control class, an increase in knowledge or N-Gain of 0.69 was obtained in the medium category. The results of the analysis of both groups used the t test at a significant level and obtained tcount = 2.315 and ttable = 1.998 so that tcalculate > ttable, then Ha is accepted meaning that there is an influence of the REACT Learning Model on student geography learning outcomes.